Оценка эффективности современной системы общественной администрирования в Сирии и возможности внедрения управления изменениями - Хурмуз, Наим (Вопросы государственного и муниципального управления, 2018)
The article analyzes the current situation in the state administration of Syria on the basis of statistical data. It is shown that the changes in the structures of the Syrian state power observed over the past few years have demonstrated the inability to change the highly decentralized, ineffi cient and non-transparent system, or to create an integral, balanced, reliable and eff ective public administration. The main shortcomings of the Syrian state now lie in its inability to provide an effective impact on the distribution of limited resources and the disparity in the distribution policy of limited resources to the prevailing public perception of justice. It is substantiated that the existing problems stemming from the poor effectiveness of the Syrian public administration authorities, taking into account resource constraints, population reduction, inflation and unemployment growth, and the growing gaps between rich and poor and rural and urban residents can be solved by introducing the technology of management of change “Point localized impact”, which seems to be an effective tool for increasing the efficiency of public authorities, the establishment of public services, and the provision of conditions for economic growth and social well-being. The article argues that the change management can ensure the development of territorial communities and the state as a whole, since the subjects of management themselves can exercise control over the areas that require improvement and development.